Analisis Pengaruh Motivasi Kerja, Iklim Kerja, Gaya Kepemimpinan, Serta Orientasi Pembelajaran Terhadap Kinerja Guru Dan Karyawan Stella Gracia School Pekanbaru - Pratama, Yandevi (Management Studies and Entrepreneurship Journal (MSEJ), 2024)
This research aims to analyze the influence of work motivation, work climate, leadership style, and learning orientation on the performance of teachers and employees of Stella Gracia School Pekanbaru. The sampling technique used in this study was a saturated sample / census with 39 respondents. The data collection method in this study used questionnaires. The data analysis techniques in this study are descriptive statistical analysis and multiple linear regression analysis with classical assumption tests. The data on the study was processed using SPSS 21. The results of this study showed that the work climate, leadership style, and learning orientation had a significant effect on the performance of teachers and employees of Stella Gracia School Pekanbaru. While work motivation does not have a significant effect on the performance of teachers and employees of Stella Gracia School Pekanbaru. This suggests the Stella Gracia School must improve its working climate, leadership style, and orientation.